A wholistic motor design philosophy for electric motorcycles in motorsport - Blissett, Jonathan (2019)
Electric vehicles combine several systems together which strive to make a performant vehicle. Improving vehicle performance is aided by modelling each subsystem not separately, but together as a whole. This work develops software for modelling the entire electro-mechanical system, able to inform the design of individual components. An electric motorcycle is chosen as a the platform for the development of such a model. Verification of the model is demonstrated by calibration to recorded data and application to a race event, demonstrating the accuracy of the modelling technique. The model guided the subsequent design of an electric motor tailored to the system, through a better understanding of the entire vehicle interaction. Applying this method to a racing motorcycle demonstrates the utility of broad system modelling in detailed component design, by guiding the determination of optimal speed and torque rating for the motor. This process demonstrated that the trend of designing increasingly high speed motors to reduce their size is not always the best approach when considering the system as a whole. The work concludes with a demonstration of the motor performance in the application, including winning a race against a mixed grid of petrol and electric motorcycles.